Pembuahan Jeruk Siam (Citrus microcarpa L.) di Luar Musim dengan Perlakuan Induksi Pembungaan dan Zat Pemecah Dormansi - RUMADA, I WAYAN; RAI, I NYOMAN; DWIYANI, RINDANG (Agrotrop : Journal on Agriculture Science, 2021)
Fertilization outside the season of Siam Orange ( Citrus microcarpa L.) with Induction of Flowering and Dormancy Breaking Substances . The Siam orange ( Citrus microcarpa L.) produces seasonal fruit with the on-season harvest from July to August while the off-season harvest, i.e. from February to September there is hardly any fruit, or very limited supply. The purpose of this study was to examine the response of flowering induction and dormancy-breaking substances to produce off-season fruits of Siam orange. This research began in April to December 2016. The experiment was arranged factorially with two factors using a randomized block design (RBD), with nine combination treatments and six replications. Flowering induction factors consist of three levels, namely I k = Control, I P = Paclobutrazol at a dose of 7.5 g/l, and I m = cutting the tip of dormant twigs. Dormancy-breaking substances factor consists of three levels, namely D k = Control, D b = BAP 200 ppm, and D n = KNO 3 300 ppm. The results of the experiment showed that the highest fruit weight per tree at off-season production was obtained by induction with paklobutrazol (28.86 kg) and the lowest was in control (12.75 kg). Flowering induction treatments was not significantly different effect on fruit quality of Siam orange, represented by weight per fruits, fruit diemater, total soluble solid and vitamine C content was not siginificant different among levels of treatment. Dormancy-breaking substances treatment also not significantly effect on fruit quality of Siam orange. Based on this research it is recommended to induce flower for off-season produce of Siam orange by pruning the tips of dormant twigs or by using paklobutrzol.